(3GdLGeY aj GdSff hGdBOGH hGdeZGRi hGdJGQjNs - (3YHO Gddg Hf CHj RjO , YHO Gddg Hf YHO GdQMef GdfZRj GdbjQhGfj, CHh eMeO,J (B386 (3g` s
(3ChdgG (B:s
(3cJGH GdLGeY HGH PcQ GdSff GdJi NdGagG GdHOY GdMeO ddg GdPi Ted GdNdb HfYeJg bGd QShd Gddg Udi Gddg Ydjg hSde JQcJ ajce CeQjf df JVdhG eG JeScJe HgeG cJGH Gddg hSfI fHjg (B" s
(3BNQgG (B:s
(3hhdO SYjO Hf GdeSjH dKdGK Sfjf ef NdGaI YeQ Hf GdNWGH Je cJGH GdLGeY ef eNJUQ CHj OQjO QMeg Gddg hHg ced LeY eNJUQ GdeOhfI hGdeNJdWI s
(3eNJUQ ef GdSeGYGJ Yf eGdc Hf CfS hef GdehWC hef ZjQ ef GdcJH eVGa Edi eNJUQ GdeOhfIs
(3fSNI Ydi ZRGds
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B73s
Keywords: (3Gdabg GdeGdcjs